Genome-wide high-throughput integrome analyses by nrLAM-PCR and next-generation sequencing - Paruzynski, Anna; Arens, Anne; Gabriel, Richard; Bartholomä, Cynthia C.; Scholz, Simone; Wang, Wei; Wolf, Stephan; Glimm, Hanno; Schmidt, Manfred; Kalle, Christof von (Nature protocols, 2010)
High-throughput integration site profiling has become a feasible tool to assess vector biosafety and to monitor the cell fate of the gene-corrected cell population in clinical gene therapy studies. Here we report a step-by-step protocol for universal genome-wide and comprehensive integrome analysis that can be performed on >102-103 samples of interest in parallel. This assay is composed of fast and cost-efficient non-restrictive linear amplification-mediated PCR; optimized sample preparation for pyrosequencing; and automated bioinformatic data mining, including sequence trimming, alignment to the cellular genome and further annotation. Moreover, the workflow of this large-scale assay can be adapted to any PCR-based method aiming to characterize unknown flanking DNA adjacent to a known DNA region. Thus, in combination with next-generation sequencing technologies, large-scale integrome analysis of >4 × 105-1 × 106 integration site sequences can be accomplished within a single week.
Gesehen am 26.06.2023